Biomechanical analysis of practitioner's gesture for peripheral venous catheter insertion. (April 2021) - Torossian, K.; Ottenio, M.; Brulez, A.-C.; Lafon, Y.; Viste, A.; Attali, P.; Benayoun, S.
Highlights: A methodology is proposed to analyze the practitioner's gesture during peripheral venous catheter insertion. Analysis of palpation and perforation motion can be used to reproduce the gesture in a more controlled fashion. Rupture and friction loads were recorded during puncture of in vivo human skin and vein. Results showed potential influence of age on vein rupture loads. Abstract: Peripheral venous catheter insertion (PVCI) is one of the most common procedures performed by healthcare professionals but remains technically difficult. To develop new medical simulators with better representativeness of the human forearm, an experimental study was performed to collect data related to the puncturing of human skin and a vein in the antebrachial area. A total of 31 volunteers participated in this study. Force sensors and digital image correlation were used to measure the force during the palpation and puncturing of the vein and to retrieve the kinematics of the practitioner's gesture. The in vivo skin rupture load, vein rupture load, and friction loads for skin only and for both the skin and vein were (mean ± standard deviation) 0.85 ± 0.34 N, 1.25 ± 0.37 N, –0.49 ± 0.19 N, and –0.51 ± 0.16 N, respectively. The results of this study can be used to develop realistic skin and vein substitutes and mechanically assess them by reproducing the practitioner's gesture in a controlled fashion.